Mongolia: Higher Education and Mobility - Loo, Bryce (International Higher Education, 2017)
Student mobility from Mongolia has increased tremendously since the early 1990s, in large part as a response to weaknesses in the domestic higher education system. Despite increased numbers, many challenges remain, including issues of brain drain and access for rural students. The Mongolian government and higher education sector can explore various options to attract back talented students and scholars overseas and utilize scholarships more effectively.